PELANGGARAN KESANTUNAN BERBAHASA DALAM DIALOG INTERAKTIF MATA NAJWA TRANS 7 EPISODE RAGU-RAGU PERPU - Ariyani, Ni Wayan Eka (Universitas Sultan Ageng Tirtayasa, 2020)
A resource person invited to a TV program should use good and polite language. However, there are still some speakers who use language that is not exemplary by the community. This study attempts to examine violations of politeness in language in an interactive dialogue Mata Najwa Trans 7episode Ragu-Ragu Perpu. This study aims to describe the shape and purpose of speech participants in violating language politeness. This research is a qualitative descriptive study. Data collection is done by listening and note-taking. The results of this study indicate that: (1) there is a violation of the maxim of praise, humility, agreement, generosity, and sympathy in interactive dialogue Mata Najwa Trans 7 episode Ragu-Ragu Perpu; 2) the violation is committed with the intention of defending the opinion of the speaker, opposing the opinion of the speech partner, boasting of the speaker, insinuating, criticizing, and cornering the speech partner. Therefore, the resource persons should be able to use good and polite language so as not to hurt the feelings of the speech partner.